Kinematic analysis of internal and external rotation range of motion in professional tennis - Schmidt-Wiethoff, R. (Medicine & Science in Sports & Exercise, 2003)
Chronic shoulder pain in overhead athletes is often caused by a failure of the kinematic chain. Various factors, such as imbalance of the scapulothoracic muscles, infraspinatus insufficiency and tightness of the posterior capsule can be responsible for kinematic chain failures. This study was designed to measure glenohumeral internal and external rotation which may be of potential etiologic importance for shoulder pathology in overhead athletes. Accordingly, we designed a new method to assess glenohumeral joint motion. A measuring system for three dimensional real time motion analysis was used for the study. The easy handling and the possibility of real time analysis make the system ideal for use in clinical studies. The data from this study demonstrate a decreased dominant shoulder IR and increased dominant arm ER in top ranked tennis players. The loss of IR is an absolute loss of motion because total rotation also decreases. The decrease in total range of shoulder motion on the dominant arm is in agreement with earlier studies on overhead or throwing athletes (1,3,4,5). The dominant arm IR deficiency has been previously described in competitive overhead athletes, utilizing goniometric measurements (1,3,4). Kibler described a loss of IR as a function of duration in elite tennis players eventually increasing with years of tournament play.5 This hypothesis could not be confirmed in our study. Ellenbecker3 examined 203 elite junior tennis players (113 males, 90 females). Bilateral goniometric measurements for internal and external rotation at 90° of abduction were performed. Analysis of IR differences showed significantly less dominant arm internal rotation for both, males and females. These results also indicate alterations of glenohumeral joint kinematics already in junior elite tennis players.